2010
DOI: 10.1213/ane.0b013e3181f2eacf
|View full text |Cite
|
Sign up to set email alerts
|

Bradycardia During Induction of Anesthesia with Sevoflurane in Children with Down Syndrome

Abstract: Bradycardia during anesthetic induction with sevoflurane was common in children with Down syndrome, with and without a history of congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 16 publications
2
19
1
1
Order By: Relevance
“…Nonetheless, some specific populations have incurred arrhythmias during sevoflurane anaesthesia. For example, up to 57% of children with Down syndrome develop bradycardia during sevoflurane anaesthesia 24. Additionally, sevoflurane prolongs the QT interval, but this is of limited clinical significance since it does not increase the dispersion of repolarisation 25.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, some specific populations have incurred arrhythmias during sevoflurane anaesthesia. For example, up to 57% of children with Down syndrome develop bradycardia during sevoflurane anaesthesia 24. Additionally, sevoflurane prolongs the QT interval, but this is of limited clinical significance since it does not increase the dispersion of repolarisation 25.…”
Section: Discussionmentioning
confidence: 99%
“…have reported that HR increases in children older than 3 years and remains unchanged in younger children and infants at 1 MAC of sevoflurane , Kraemer et al . have noticed a 12% incidence of bradycardia following sevoflurane induction in healthy children with the time to the HR nadir of 196 ± 116 s . Our study showed that two patients in the placebo group (#8 and # 9) responded with a decrease in HR at two MAC of sevoflurane with a nadir approximately at 1 min following the anesthetic induction (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Se ha descrito una mayor frecuencia de bradicardia en estos niños al recibir inducción anestésica con sevoflurano, independiente de la coexistencia de cardiopatía 38 . Habitualmente ésta es de fácil corrección y no se asocia a un peor pronóstico 39 .…”
Section: Patología Cardíacaunclassified